Perlindungan Hukum Pidana terhadap Jurnalis Ni Luh Anggela yang Mengalami Doxing oleh Akun @Greschinov di Media Sosial Instagram - Rijal Apriani (Lembaga Pengembangan Kinerja Dosen, 2025)
In the ever-evolving digital age, the dissemination of personal information through social media has become an important issue, especially for journalists. One form of crime that has emerged is doxing, which is the collection and publication of a person's personal data for the purpose of intimidation. The doxing case against Ni Luh Anggela, a journalist in Indonesia, by the Instagram account @greschinov, is in the spotlight because it shows the vulnerability of journalists to cyber attacks. This study aims to analyze the criminal law protection available to Ni Luh Anggela and the legal steps she can take. The method used is normative juridical with a statutory approach and literature study. The results showed that the act of doxing by @greschinov fulfilled the elements of a criminal offense according to the Electronic Information and Transaction Law and the Personal Data Protection Law.